Epidemiological Study on Salmonella Prevalence in Sow Herds Using Direct and Indirect Detection Methods - Isabell Hollmann; Jan Berend Lingens; Volker Wilke; Christian Homann; Klaus Teich; Juhle Buch; Bussarakam Chuppava; Christian Visscher (Microorganisms, 2022)
In piglet production, the beginning of pork production, Salmonella prevalence requires greater attention as having an impact on the subsequent production steps. The aim of this study was to investigate Salmonella prevalence in three sow herds with attached piglet rearing units. Salmonella prevalence was investigated either directly by boot swabs and feces or indirectly by serum samples taken during gilt integration, the peripartal period, and piglet rearing. Boot swabs and feces were analyzed by real-time PCR and subsequent microbiology. Results indicated that high biosecurity measures in sow husbandry do not necessarily result in a low Salmonella prevalence. Furthermore, the sow herds’ Salmonella prevalence should not be used to infer the situation in the associated piglet rearing. The proportion of positive boot swabs was 10.5, 3.6, and 21.3% for sows (gilts and peripartal) with an inverse situation in piglet rearing with 50.0, 63.3, and 5.8% positive swabs for farms A, B, and C, respectively. Boot swabs are suitable as a direct sampling method to gain an overview of Salmonella prevalence in both sows and piglets. Indirect serum antibody testing can be useful, although it should be evaluated considering age-dependent levels of antibody titres.